Bruxism in Childhood: A Scoping Review - Cristine da Silva Furtado Amaral; Jennifer Guedes Sobral; Flávia Cariús Tesch Ferreira Alves; Claudia Maria Pereira; Flávio Rodrigues Ferreira Alves (Taylor & Francis Group, 2024)
ABSTRACTBruxism is characterized by repetitive clenching or grinding of teeth and jaw muscle activity. It is a complex condition with various factors contributing to its development and can exert abnormal loads on the stomatognathic system.Aim This scoping review aimed to explore various aspects of bruxism in children, including its causes, prevalence, diagnosis, and multidisciplinary treatment.Methods A comprehensive search was conducted in the PUBMED-MEDLINE database focused on studies published from 2018 to 2023.Inclusion criteria encompassed Cross-sectional, longitudinal, comparative studies, and randomized and non-randomized clinical trials published in English. Retained full texts were assessed and excluded if inclusion criteria were not met. Methodological quality was assessed using the Joanna Briggs Institute critical appraisal tools for the different types of studies.Results Of 498 initial studies, 26 were selected for full reading and 19 met the inclusion criteria. Most studies were cross-sectional (14 studies) and showed a wide prevalence of sleep bruxism.Conclusion This scoping review highlights that bruxism is an important issue in children that should be observed by parents/guardians and evaluated by health professionals. Due to its multifactorial nature, a collaborative approach involving a diverse team of professionals is essential for the effective prevention and treatment of bruxism in pediatric patients.